Character Values In General Education At University - Hidayat, Mupid; Rozak, Rama Wijaya Abdul; Maftuh, Bunyamin; Kembara, Maulia Depriya; Hadian, Vini Agustiani (Jurnal Pendidikan Ilmu Sosial, 2022)
The research objective focuses on examining the character values contained in the Compulsory Curriculum Subjects or Mata Kuliah Wajib Kurikulum (MKWK). Content analysis and Focus Group Discussions (FGD) attended by education experts. The results of the analysis show that there are 24 characters values contained in the MKWK. These character values are developed through four courses in MKWK, namely Indonesian Language Education, Islamic Religious Education, Citizenship Education, and Pancasila Education. Each of these courses has a unique character that is developed in learning. The findings were presented in FGDs and assessed by experts based on the character's priority scale. The FGD produced two aspects of character, namely individual characters and social characters. Each aspect of the character has several types of characters that must be developed by students. The type of character in the individual aspects, namely religious, self-aware, and intellectual. Characters in the social aspect include polite, tolerant, participatory, democratic, and fair. These characters are the external characteristics of MKWK learning.